Improving durability of silicone-based paint coatings used in solar power plants by controlling consolidation procedures. (15th March 2020) - Martínez, N.; Rico, A.; Múnez, C.J.; Prieto, C.; Poza, P.
Graphical abstract: Highlights: Pyromark durability is established to be dependent on the curing and vitrification. Two Curing and vitrification processes are performed in oven and IR radiation. Time-dependent mechanical properties are measured by depth sensing indentation. Glass transition temperature, relaxation times, and wear rates are related. Durability of Pyromark is improved with a proper consolidation procedure. Abstract: Pyromark is a silicone-based black paint that is commonly used in concentrated solar power plants because of its relatively high absorptivity. However, it has very low durability, which decreases the optical performance of the surfaces coated with this paint over time, thus reducing the thermal efficiencies of these plants. Recent studies have tried to develop promising materials to circumvent this problem; however, there is no commercial substitute for Pyromark as yet. Therefore, improving the durability of this paint is necessary to enhance the power plants operation. In this work, we study the durability of Pyromark through the micro-wear performance of the coatings assessed by scratch tests. Curing and vitrification procedures control the physical and mechanical properties of the manufactured coatings. For the first time, we demonstrate that the time-dependent behavior and related properties such as the material relaxation times are key parameters controlling the durability of this type of paint. The ability of the material to store elastic energy also explains why some consolidation procedures are better to increase its durability.